Absolutism in Renaissance Milan plenitude of power under the Visconti and the Sforza, 1329-1535 - Black, Jane, 1945- (Oxford University Press, 2009)
Jane Black shows how authority above the law, once the preserve of pope and emperor, was seized, exploited, and eventually relinquished, by the ruling Milanese dynasties. Lawyers supported the free use of absolute power at first, but both sides realised that society could not function unless property and other rights were respected.